Early experience with uniportal robotic thoracic surgery lobectomy - Mercadante, Edoardo; Martucci, Nicola; De Luca, Giuseppe; La Rocca, Antonello; La Manna, Carmine (Frontiers in Surgery, 2022)
Background. Invasiveness is considered one of the cornerstones in every field of surgery and Video-assisted thoracoscopic (VATS) approaches are now routinely used worldwide to perform pulmonary resections. Recently, robotic-assisted thoracic surgery (RATS) is becoming the preferred technique in many centers but it is routinely performed using 3 or 4 ports with at least one service incision, being in contrast with the real concept of invasiveness, especially if compared to uniportal VATS (U-VATS). Hereby we present our early experience with uniportal RATS (U-RATS) pulmonary resections for early-stage lung cancer. Technical details of surgical steps are accurately described and commented. Results. Twenty four consecutive patients with lung cancer underwent U-RATS anatomical pulmonary resections at our Institute. All procedures were completed with uniportal approach. Mean operative time was 210 minutes (range 120-350); in the last 10 cases the operative time was significantly reduced (180 minutes) compared to the first 10 cases (232 minutes) (p< 0.02), showing a very fast learning curve. Post-operative pain score was comparable to U-VATS and was constantly low. Conclusions. U-RATS is a safe and feasible technique, combining the advantages of U-VATS to the well-known advantages of robotic surgery.